Consumer Life and User Generated Content in the Age of Social Media - CHEREGI, Bianca-Florentina (Management Dynamics in the Knowledge Economy, 2018)
The rise of social media and the emergence of globalization has changed the relationship between brands and consumers. The aim of this paper is to discuss how is this relationship affected by user generated content (UGC) and user generated brands (UGB). Consumers tend to look for products and brands in order to construct and sustain their social self. In this regard, the brand can define a person with respect to others. The brand constitutes a vital entity in the consumer’s mind, acting as an enlivened partner in a relationship, and contributing to the initiation, maintenance, and destruction of the consumer-brand bond. In this context, the paper insists on the idea of brand personality, as developed by Jennifer Aaker (1997), connecting it to consumer culture studies. The research is based on a set of semi-structured interviews with 10 advertising creatives working at some of the most important Romanian advertising agencies. The investigation instrument used was the computer-assisted interview (CASI). The results point in the direction of a constructed brand personality, promoting an active and involved consumer. Advertisers have the power to define brands personality, inviting users to create content as well. The meaning of the brand is linked with the culture in which a particular sign is decoded. Advertisers give people hints of who is the brand, what is its core activity, its cultural references, set of values or personality traits. Brands have a personality and by communicating it, the character is build up gradually. In fact, brands tend to build a reflection or an image of the consumer which it seems to be addressed through the advertising messages.